Barriers for nurse participation in multidisciplinary ward rounds: An integrative review - Vahid Zamanzadeh; Samira Orujlu; Raziyeh Beykmirza; Marjan Ghofrani (Tehran University of Medical Sciences, 2020)
Background & Aim: The purpose of this integrative literature review was to find, critically evaluate, and describe publications about barriers against nurse participation and collaboration in multidisciplinary ward rounds. Although multidisciplinary ward rounds are the right place for doctors and nurses to communicate, nurses' attendance in these rounds is missed. The nurses' absence at the multidisciplinary ward rounding has apparent negative effects on the patients, their relatives, other team members, and patients' care. Methods: A systematic approach to searching, screening, and analyzing the literature was applied. The original and review papers were used. This study was an integrative review based on Whittemore and Knafl's framework. Web of Science, PubMed, Scopus, Cochrane, Magiran, and SID were searched by time limitation for ten years (2009-2019). The search was conducted between February 2019-March 2019. The language was limited to English and Persian. Results: After duplicate removal, title, and abstract review, 63 papers remained. After full-text control, finally, 7 papers chased for this review. Barriers for rounding were divided into 4 main categories: time limitation, reluctance to participate, ineffective communication, and infrastructure & administration. Nurse time limitation, feeling not being valued by MDs, lack of standard and structure, and nurse unawareness from time of round are the most repeated barriers.  Conclusion: Barriers may need to be removed until nurse participation in multidisciplinary ward rounds improves. Some study needs to take place about this issue in Iran to identify the situation, facilitators, and barriers specific to our country. Based on them, a relevant intervention can be chased.